Manajemen Pemanfaatan Website dan Instagram Sebagai Sarana Promosi untuk Meningkatkan Branding Sekolah - Siti Aisyah; Hidayati, Dian; Budi Santosa, Achadi; Widodo, Hendro (Universitas Muhammadiyah Surakarta, 2024)
In the field of education, social media has a contribution to improving school branding. SMA Muhammadiyah 4 Bandung city took advantage of this opportunity as a means of promoting the school to make it better known to the wider community. The aim of this research is to determine the use of school websites and Instagram as promotional tools to improve school branding. This research uses a qualitative method with a descriptive approach. he instruments used in this research were the principal, deputy principal for Student Affairs, deputy principal for Public Relations, website and Instagram admin. The results of this research are that schools utilize social media, especially websites and Instagram, optimally with comprehensive management; consist of good planning, clear organization, implementation that follows the school's agenda both intra and extra, as well as regular evaluation. The effectiveness of website and Instagram media can be seen from the number of views, likes, comments and additional followers from regular and continuous posts, which also has an impact on the top position in Google searches and the Instagram application. There are several obstacles in optimizing the use of school accounts, but there are future plans to develop and improve these social media accounts for optimal results in promoting school branding